Wear and biological effects of a semi-constrained total disc replacement subject to modified ISO standard test conditions. (April 2015) - Hyde, P.J.; Tipper, J.; Fisher, J.; Hall, R.M.
Abstract: Development of pre-clinical testing methodologies is an important goal for improving prediction of artificial replacement joint performance and for guiding future device design. Total disc replacement wear and the potential for osteolysis is a growing concern, therefore a parametric study on the effects on wear of altered kinematics and loading was undertaken. A standard ISO testing protocol was modified in order to study the wear behaviour of lumbar total disc replacements when subject to low cross shear input kinematics, reduced axial loading and smaller flexion–extension magnitude. Volumetric wear, bearing surface topography, and wear debris biological reactivity were assessed. The ISO standard results were expected, however, the very low cross shear test produced a level of wear approximately two orders of magnitude higher than that reported for zero cross shear motions on UHMWPE bearings. When the osteolytic potential of the wear particles was calculated, all total disc replacement simulations had lower predicted osteolytic potential compared to total hip replacements, as a consequence of the generally lower wear rates found. Graphical abstract: Highlights: A lumbar total disc replacement assessed for wear and biological effects of wear. A very small amount of crossing path motion produced significant wear. Lowered load and reduced kinematics reduced wear to a lesser extent. Wear debris was similar to hip debris and therefore has osteolytic potential.